Conclusions - Deutz, Pauline (2024)
Publisher Copyright: © 2025 selection and editorial matter, Pauline Deutz, Walter J.V. Vermeulen, Rupert J. Baumgartner, Tomás B. Ramos, and Andrea Raggi; individual chapters, the contributors.